2012
DOI: 10.1097/iae.0b013e31821800b9
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic Isoforms of Vascular Endothelial Growth Factor Predominate in Subretinal Fluid of Patients With Rhegmatogenous Retinal Detachment and Proliferative Vitreoretinopathy

Abstract: The absence of an increased ratio of VEGF xxx to VEGF xxx b in patients with PVR as compared with patients with uncomplicated rhegmatogenous retinal detachment may explain a lack of blood vessels in PVR membranes. Elevated VEGF levels indicate that this cytokine may play a role in the pathogenesis of PVR that is not related to angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The paradox of increased VEGF levels in an avascular process like PVR can be explained by observations by Ricker et al[24] and Perrinet al[25] which showed that antiangiogenic isoforms of VEGF (so-called VEGF xxx b) account for the majority of the total VEGF. These isoforms are products of splicing in the C-terminal exon and inhibit proliferative and vasodilator effects of VEGF 165 .…”
Section: Discussionmentioning
confidence: 99%
“…The paradox of increased VEGF levels in an avascular process like PVR can be explained by observations by Ricker et al[24] and Perrinet al[25] which showed that antiangiogenic isoforms of VEGF (so-called VEGF xxx b) account for the majority of the total VEGF. These isoforms are products of splicing in the C-terminal exon and inhibit proliferative and vasodilator effects of VEGF 165 .…”
Section: Discussionmentioning
confidence: 99%
“…As these structures form, they may physically attach to the retina, contract, and cause retinal tears. Support for this hypothesis stems from the presence of many growth factors and cytokines in the pathological vitreous or epiretinal membrane, including platelet-derived growth factor (PDGF) isoforms [21, 22], hepatocyte growth factor (HGF) [22, 23], vascular endothelial growth factor (VEGF) [24], epidermal growth factor (EGF) [25], pigment epithelium-derived factor (PEDF) [26], transforming growth factor β (TGF β ) [27, 28], tumor necrosis factor α (TNF α ) [29, 30], TNF β [29], granulocyte colony-stimulating factor (G-CSF) [29], fibroblast growth factors (FGF) [29, 31], basic fibroblast growth factor (bFGF) [32], insulin [25], insulin-like growth factor-1 (IGF-1) [33], connective tissue growth factor (CTGF) [22, 23], glutamine synthetase [32], interleukin 1 (IL-1) [34], IL-6 [29, 31], IL-8 [29, 35], IL-10 [29], interferon γ (IFN γ ) [28, 29], monocyte chemotactic protein [35, 36], macrophage-colony stimulating factor [35], granulocyte colony-stimulating factor (G-CSF) [29], chemokine ligand 2 (CCL2) [29], CCL3 [29], CCL4 [29], CCL5 [29], and protein [31]. …”
Section: The Growth Factor and Cytokine Hypothesis For Developmentmentioning
confidence: 99%
“…VEGF levels were found to be higher in subretinal fluid and vitreous fluid samples of PVR compared with uncomplicated RRD. [9][10][11][12][13] Considering the role of VEGF in the pathogenesis of PVR, it is rational to consider anti-VEGF medications as a potential modality for prevention of PVR.…”
Section: Introductionmentioning
confidence: 99%